P3.408 Sex Work Involvement Predicts Poor Viral Load Suppression Among People Who Inject Drugs in a Canadian Setting. (13th July 2013) - Ti, L; Milloy, M; Shannon, K; Kerr, T; Simo, A; Montaner, J; Wood, E
Abstract : Introduction: In addition to its role in HIV disease progression, recent studies have demonstrated the crucial function of plasma HIV-1 RNA viral load (pVL) on HIV transmission. However, there is limited empiric research on virologic outcomes among people who use illicit drugs (PWID) and are engaged in sex work. The main objective of this study was to investigate the relationship between sex work and pVL suppression among PWID in Vancouver, Canada. Methods: Data were derived from the AIDS Care Cohort to evaluate Exposure to Survival Services (ACCESS), an ongoing prospective cohort of HIV-positive PWID linked to comprehensive clinical information in a setting of universal no-cost HIV care. Using generalised estimating equations (GEE), we studied the longitudinal relationship between sex work and pVL suppression, defined as < 500 copies HIV RNA per millilitre. In addition, we tested whether adherence to antiretroviral therapy (ART) mediated the relationship between sex work involvement and pVL suppression. Results: Between May 1996 and May 2012, 608 ART-exposed participants were included in the study and completed 2458 person-years of observation. In a multivariate model adjusted for possible confounders, sex work was independently associated with poorer odds of pVL suppression (Adjusted Odds Ratio [AOR] = 0.65; 95% confidence interval [CI]: 0.46 – 0.92). Using a validated measure of pharmacy refill, we found that adherence mediated this relationship (Sobel test statistic = 4.44, p < 0.01). Conclusions: In this study, we found that PWID were less likely to experience virologic control during periods of engagement in sex work, a relationship mediated by adherence. In light of these findings, interventions to improve adherence to ART among individuals engaged in sex work are urgently needed to help produce the maximum HIV treatment and prevention benefit of ART among PWID.